Mathematical ideas embedded in water debit practices of sand sellers in Ciseupan: An ethnomathematics study - Muthia, Shahla Naila; Maulani, Indria (CV. Pustaka Literasi Ilmiah, 2025)
Indonesia is a country rich in local cultural practices that not only reflect traditional values but also hold great potential for the development of contextual learning based on local wisdom. One such form of wisdom is reflected in the economic activities of the community of Kampung Ciseupan, South Cimahi, in the form of sand sales practices that have been passed down from generation to generation and contain various mathematical concepts that have not been widely explored. This study aims to explore the mathematical concepts embedded in these cultural practices, particularly the concept of flow rate that emerges in sand loading and unloading activities. The approach used is ethnography, in line with the principles of ethnomathematics, which examines mathematical practices from the perspective of the cultural practitioners themselves. Data was collected through field observations and semi-structured interviews with the main participant, Mrs. LM, a sand seller. The researcher served as the primary instrument in observing, exploring, and analyzing the connection between cultural activities and mathematical concepts. The research findings indicate that sand selling activities contain concepts of debit, volume, distance, speed, and time that are implicitly present in community practices. These findings suggest that local culture can serve as an authentic, contextual, and relevant source of mathematical learning for students' daily lives, and can encourage students to understand and appreciate their own culture.